2010
DOI: 10.1007/s11745-010-3385-4
|View full text |Cite
|
Sign up to set email alerts
|

DGAT1, DGAT2 and PDAT Expression in Seeds and Other Tissues of Epoxy and Hydroxy Fatty Acid Accumulating Plants

Abstract: Triacylglycerol (TAG) is the main storage lipid in plants. Acyl-CoA: diacylglycerol acyltransferase (DGAT1 and DGAT2) and phospholipid: diacylglycerol acyltransferase (PDAT) can catalyze TAG synthesis. It is unclear how these three independent genes are regulated in developing seeds, and particularly if they have specific functions in the high accumulation of unusual fatty acids in seed oil. The expression patterns of DGAT1, DGAT2 and a PDAT in relation to the accumulation of oil and epoxy and hydroxy fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
115
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 69 publications
7
115
1
1
Order By: Relevance
“…m e a n _ W T m e a n _ D (Li et al 2010b;Turchetto-Zolet et al 2011). Our results show that both JcDGAT1 and JcDGAT2 were able to restore TAG synthesis in the yeast cell and tobacco, reflecting the functional similarity of JcDGAT1 and JcDGAT2 in TAG biosynthesis.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…m e a n _ W T m e a n _ D (Li et al 2010b;Turchetto-Zolet et al 2011). Our results show that both JcDGAT1 and JcDGAT2 were able to restore TAG synthesis in the yeast cell and tobacco, reflecting the functional similarity of JcDGAT1 and JcDGAT2 in TAG biosynthesis.…”
Section: Discussionmentioning
confidence: 58%
“…To our knowledge, this is the first report on the substrate preference of DGAT2 to linoleic acid in plants. Previous studies also showed that RcDGAT2, VgDGAT2 and VfDGAT2 played a major role in TAG assembly of hydroxy or epoxy fatty acids in developing seeds (Shockey et al 2006;Burgal et al 2008;Li et al 2010b). It seems that DGAT2s have a greater contribution to accumulation of specific fatty acid compositions of TAG in planta than DGAT1s.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Many efforts from both industrial and academic laboratories have been directed toward producing oxygenated fatty acids in oilseed crops. Current oilseed crops, such as soybean, rapeseed, and sunflower, do not produce hydroxy fatty acids or any other oxygenated fatty acid naturally (43). Yeast cells expressing At5g23940 were grown in the medium containing hydroxy fatty acid, which resulted in the incorporation of fatty acid into TAG.…”
Section: Gc-ms Analysis By Feeding the Cells With 16-hydroxyhexadecanoicmentioning
confidence: 99%